Abstract Model Checking of tccp programs - Alpuente, María; del Mar Gallardo, María; Pimentel, Ernesto; Villanueva, Alicia (Electronic notes in theoretical computer science, 2005)
The Timed Concurrent Constraint programming language (tccp) introduces time aspects into the Concurrent Constraint paradigm. This makes tccp especially appropriate to analyze by model checking timing properties of concurrent systems. However, even if very compact state representations are obtained thanks to the use of constraints in tccp, large state spaces can be still generated which may prevent model checking tools from verifying tccp programs completely. In this paper, we introduce an abstract methodology which is based on over- and under-approximating tccp models and mitigates the state explosion problem which is common to traditional model checking algorithms. We ascertain the conditions for the correctness of the abstract technique and show that, due to the timing aspects of the language, this semantics does not correctly simulate the suspension behavior, which is a key feature of tccp. Then, we present a refined abstract semantics which correctly models suspension.